The historical development of Anglo-Italian trade - SAUL, S.B. (PSL Quarterly Review, 2014)
The article describes the way in which the pattern of trade between Italy and the United Kingdom has reacted to the pace and character of economic growth in each of the two countries. The author begins by giving a brief account of the character of trade between the two countries up to the middle of the last century, but concentrates mainly on developments since that time. The changes in the volume and composition of British exports to Italy after 1850, under the influence of industrialisation, of Italian tariff policy, of the growth of German competition, and of the developments in Italian economic activity, are first traced. The author goes on to describe the main lines of development in British imports from Italy, providing a brief sketch of the pre-1914 pattern of surpluses and deficits of Britain and Italy, with various countries. The inter-war period is then analysed, highlighting the effects of the Italian tariff of 1921, the fall in the share of the United Kingdom in Italian import trade, and the decline in the U.K. export surplus with Italy, which were evident in the twenties, and finally, to the all-round decline in Anglo-Italian trade which took place in the latter half of the thirties. A summary of the shifts in the net Anglo-Italian trading position since the Second World War are provided in conclusion. JEL: F10, F13, N73, O14